The Use of Information and Communication Technologies in Teaching Economics to Students in Basic School - Vasilenko, Timofey Andreevich (Razvitie obrazovaniâ (Online), 2020)
The author of the article outlines that the problem of teaching methods is one of the most important in pedagogical science and practice of school teaching, since teaching methods are the main tools with which a tutor teaches the basics of science to students, develops their cognitive abilities, ensures personal development and forms a scientific worldview. The article formulates the role of information and communication technologies (ICT) in the educational process. The pedagogical experiment of using ICT in teaching economics to primary school children is described. The purpose of the research is to form economic knowledge in primary school children using information and communication technologies. Method of research. The following methods were used in the study: comparison, analysis, observation and experiment. The experiment was conducted among 24 schoolchildren who were divided into a control and experimental group. A variety of ICTs were used: an interactive whiteboard, reference and multimedia Internet resources, social networks, various messengers, presentations made in the Microsoft Power Point program, as well as using the Prezi service. Research result. In the control group, the average level of economic knowledge increased by more than 40%. The number of schoolchildren with an average and high level of economic knowledge in the experimental group increased by 3 and 2.5 times. Conclusions are made about the possibility of using ICT in teaching economics to school children.